ANALISIS USABILITY PADA APLIKASI EDULOGY MENGGUNAKAN SYSTEM USABILITY SCALE (SUS) STUDI KASUS DI SMA NEGERI 5 KOTA JAMBI - amin, muhammad (Prodi Sistem Informasi FST Universitas Jambi, 2021)
This study aims to identify the usability or usability of the Edulogy application using the System Usability Scale (SUS) at SMA Negeri 5 Jambi City. Respondent criteria used in this study were students and teachers who used the Edulogy application for learning media boldly at SMA Negeri 5 Jambi City. The data used are primary data sourced from respondents of 81 teachers and 304 students. The calculation technique used is by using the System Usability Scale (SUS) calculation. The results of the calculations in this study found that the System Usability Scale (SUS) can explain 72 SUS scores obtained from teachers and 68 SUS scores obtained from students in the Edulogy application. . In the second grade, the SUS score can be seen to be in Grade C (okay) which indicates the score is normal, neither above nor below average. In the adjectives, it can be achieved that the Eduology learning according to the respondents is classified as normal. In Acceptability the use of the Edulogy application can be accepted and used in general by respondents and on the Net Promoter Score (NPS) it is in the passive classification.